Influence of different Ni nanolayers thicknesses on single oscillator model parameters, optical band gap, and disordering energy in CNTs synthesized by Cu‐Ni @ a‐CH catalyst. (14th September 2021) - Dalouji, Vali; Goudarzi, Samira
Abstract : In this paper, Cu‐Ni NPs @ a‐C:H thin films with different Ni layers thickness by co‐deposition of RF‐sputtering and RF‐plasma enhanced chemical vapor deposition (RF‐PECVD) were prepared using acetylene gas and Ni and Cu targets. The absorption edge and the optical dispersion parameters in CNTs synthesized by Cu‐Ni @ a‐C:H catalyst were studied. RBS measurements were performed, which confirmed the presence of Ni and Cu atoms in these films. Using Atomic Force Microscopy (AFM) system, the morphology of the films surface was investigated. The average diameter of the grown CNTs on Ni‐Cu NPs @ a‐C:H substrates were increased by increasing of Ni layers thickness. The values of dT/dλ and dR/dλ for grown CNTs without Ni show that the minimum value of the optical band gap corresponds to values of 2.55 and 2.56 eV, respectively. The absorption spectra peaks of films are about 400‐600 nm. These peaks are quite sharp for carriers band to band transitions and with increasing Ni layers thickness, there is a small shift. It can be seen that the dispersion energy Ed and the oscillator strength 𝑓 of CNTs synthesized by Cu‐Ni @ a‐C:H catalyst had the lowest values of 2.21 eV and 9.39 eV 2, respectively, compared to the other films.